Analisis Pola Komunikasi Guru–Siswa dalam Manajemen Kelas pada Pembelajaran Seni Berbasis Nilai Silih Asah, Silih Asih, Silih Asuh di SDIT Nabawi - Aulia Zahra, Shirly; Kurnia, Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teacher–student communication patterns in classroom management within art learning based on the values of silih asah, silih asih, and silih asuh at SDIT Nabawi. This study employed a qualitative approach with a descriptive method. The research subjects consisted of teachers and students, and the data were collected through observation, interviews, and documentation. The results show that the communication patterns applied by the teacher are interactive and humanistic, reflecting the values of silih asah (mutual learning), silih asih (mutual care), and silih asuh (mutual guidance). The implementation of these communication patterns contributes to creating a conducive classroom atmosphere, increasing student engagement, and strengthening the emotional relationship between teachers and students. Thus, effective communication based on local cultural values plays an important role in supporting successful classroom management, particularly in art learning at the elementary school level.